Efforts to Determine Career Choices for Vocational Students with the Career Information Service Module - Yustina Misaria Tarigan; Luh Putu Sri Lestari (Bisma The Journal of Counseling, 2023)
Many students who are confused about choosing a career after completing their vocational education level are influenced by the lack of career information counselors provide. This research aims to develop and test the practicality of a career information service module for determining career choices for SMK students. This research belongs to the type of development research that was developed using the ADDIE model. The ADDIE development model comprises five stages: analysis, design, development, implementation, and evaluation. The subjects involved in this study were three experts in the field of counseling guidance, two guidance counseling teachers, and 30 students. Data collection in the study was carried out using observation and questionnaire methods, with research instruments in the form of questionnaire product validity sheets about career selection. The data obtained in the study were then analyzed using product validity analysis techniques using the CVR method, followed by calculating the CVI. The product acceptance test was analyzed using PAIT analysis. To determine the module's effectiveness, the data were analyzed by t-test with the help of SPSS Windows 20. The results obtained in the study showed that the sig score was 0.677. This probability score is smaller than the 0.05 significance level. These results indicate that the career information service module effectively determines career choices for SMK students.